Ontogeny reveals function and evolution of the hadrosaurid dinosaur dental battery. Issue 1 (December 2016) - LeBlanc, Aaron; Reisz, Robert; Evans, David; Bailleul, Alida
Abstract Background Hadrosaurid dinosaurs, dominant Late Cretaceous herbivores, possessed complex dental batteries with up to 300 teeth in each jaw ramus. Despite extensive interest in the adaptive significance of the dental battery, surprisingly little is known about how the battery evolved from the ancestral dinosaurian dentition, or how it functioned in the living organism. We undertook the first comprehensive, tissue-level study of dental ontogeny in hadrosaurids using several intact maxillary and dentary batteries and compared them to sections of other archosaurs and mammals. We used these comparisons to pinpoint shifts in the ancestral reptilian pattern of tooth ontogeny that allowed hadrosaurids to form complex dental batteries. Results Comparisons of hadrosaurid dental ontogeny with that of other amniotes reveals that the ability to halt normal tooth replacement and functionalize the tooth root into the occlusal surface was key to the evolution of dental batteries. The retention of older generations of teeth was driven by acceleration in the timing and rate of dental tissue formation. The hadrosaurid dental battery is a highly modified form of the typical dinosaurian gomphosis with a unique tooth-to-tooth attachment that permitted constant and perfectly timed tooth eruption along the whole battery. Conclusions We demonstrate that each battery was a highly dynamic, integrated matrix of living replacement and, remarkably, dead grinding teeth connected by a network of ligaments that permitted fine scale flexibility within the battery. The hadrosaurid dental battery, the most complex in vertebrate evolution, conforms to a surprisingly simple evolutionary model in which ancestral reptilian tissue types were redeployed in a unique manner. The hadrosaurid dental battery thus allows us to follow in great detail the development and extended life history of a particularly complex food processing system, providing novel insights into how tooth development can be altered to produce complex dentitions, the likes of which do not exist in any living vertebrate.